The Prevent Scabies with Healthy Living - Isnaini, Isnaini; Rosida, Azma; Widyamala, Erida (Asian Journal of Community Services, 2024)
One of the skin diseases often experienced by the community of Keliling Benteng Ulu RT.09 is scabies. Scabies is an infectious skin disease caused by female mite Sarcoptes scabiei varieta hominis. This community service activity is to provide education about scabies. This activity is carried out by providing education about scabies, how to prevent and treat it. In this activity, a pre-post test will be carried out to determine changes in knowledge. The pre-post test results showed an increase in knowledge by 79%. Service participants have begun to understand the definition, causes, symptoms, treatment of scabies and its prevention through a healthy lifestyle. Conclusion community service activities run smoothly, series of health counseling also provides great benefits for participants.